The Marginal Cost of Saving a Life in Health Care: Age, Gender and Regional Differences in Switzerland - Stefan Felder; Andreas Werblow (Swiss Journal of Economics and Statistics, 2009)
We estimate the marginal cost of life using age- and gender-specific health care expenditures and mortality rates of the 26 Swiss cantons for the period 1997 to 2006. We show triple the marginal cost of saving a life for women as compared to men, reflecting a lower marginal elasticity of medical inputs, a lower mortality rate and higher spending on health care for women. Medical technology does not differ across cantons while the marginal cost of saving a life does. Wealthy cantons spend more on saving a life at the margin and show a smaller gender gap in longevity.
Keywords: H11; I12; I18; J16; 330; Marginal cost of saving a life; value of a statistical life; gender; health production; regional diversity